PENGARUH CAR, NPF DAN FDR TERHADAP PROFITABILITAS BANK SYARIAH (Studi Kasus Pada Bank BCA Syariah Tahun 2010-2017) - Abdul Haris Romdhoni; Bunga Chairunisa Chateradi (JURNAL ILMIAH EDUNOMIKA, 2018)
This study aims to determine the effect of Capital Adequacy Ratio (CAR), Non Performing Financing (NPF), Financing to Deposit Ratio (FDR) to profitability at Bank BCA Syariah year 2010-2017 either partially or simultaneously. The population in this study is Bank BCA Syariah in 2010-2017 as many as 30 samples taken by purposive sampling. Data used using secondary data obtained from quarterly financial report of Bank BCA Syariah. The method used in this research is by using classical assumption test method where the classical assumption test consist of four test that is Normality test, Multicolinierity test, Heterokedasticity test, Autocorrelation test besides using Classic Assumption test, in this research also use test with data analysis from analysis multiple linear regression and using t test or partial test and F test or together. The results showed that the variables affecting profitability are Capital Adequacy Ratio (CAR) with P-value of 0.000 and t-count equal to -4.206 where this value is bigger than t-table 2.05553, while the variable that has no effect on profitability is a Non Performing Financing (NPF) variable with a value of P-value of 0.105 where this value is greater than 0.05 and t-count is smaller than t-table and Financing to Deposit Ratio (FDR) variable with P-value value of 0.362 where this value is greater than 0.05 and t-count is smaller than t-table. Simultaneously all variables CAR, NPF and FDR jointly affect the profitability of Bank BCA Syariah year 2010-2017. Keywords: Capital Adequacy Ratio (CAR), Non Performing Financing (NPF), Financing to Deposit Ratio (FDR), Profitability.